The Influence of Leadership Style, Work Motivation, and Job Satisfaction on Educator Performance at SMK Syafi'i Akrom, Pekalongan City - Wildan Ahmad; M. Maulidin Fachrur (Business, Accounting, and Knowledge Journal, 2025)
This research aims to test and analyze the influence of leadership style, work motivation and job satisfaction on employee performance. The type of research used in this research is causal research. The population in this study were all teachers at SMK Syafi'i Akrom, Pekalongan City. The sampling technique in this research used saturated sampling (census), so the samples taken in this research were all teachers at SMK Syafi'i Akrom, Pekalongan City, totaling 73 teachers. The type of data used in this research is primary data. Data collection was done by distributing questionnaires online. The analysis techniques used are Instrument Test, Classic Assumption Test, Model Fit Test, Multiple Linear Regression Analysis and Hypothesis Test (t Test) with the help of the SPPS Version 20 program. The results of this research can be concluded that leadership style has a positive and significant effect on the performance of educators at Syafi'i Akrom Vocational School, Pekalongan City. Work motivation has a positive and significant effect on the performance of educators at Syafi'i Akrom Vocational School, Pekalongan City. Job satisfaction has a positive and insignificant effect on the performance of educators at Syafi'i Akrom Vocational School, Pekalongan City.